Assessing Climatic Variability in Data scare regions of Morocco: Drought Periods and Exceptional Precipitation Events - Brahim Bougdira; Badr Layan; Sadik El Yadari; Mohamed Ben Abbou; Nessraddine Adouk; Lahcen Benaabidate (European Scientific Journal, ESJ, 2025)
The southern Mediterranean region is characterized by significant climatic variability, which profoundly affects precipitation patterns, a critical water resource. To explore this variability, we conducted a comprehensive statistical analysis of the upper Larbaâ basin, situated at the edge of the Eastern Rif Mountains. This area has been experiencing atypical weather events, including sudden flooding and extended drought periods. Our research involved a thorough analysis of monthly and annual precipitation data spanning 65 years, from 1958 to 2023. The homogeneity test revealed a disturbance in the time series from the late 1970s to the early 1980s across all monitored rainfall stations. Utilizing the Moving Average and Inverse Distance Weighting (IDW) model, we identified variations in rainfall amounts, demonstrating a notable trend from the southwest to the northeast of the basin. Furthermore, correlation analysis between precipitation levels and the North Atlantic Oscillation (NAO) index showed an inverse relationship, particularly evident in the northwestern section of the watershed. The EM index indicated a drought duration ranging from 33 to 36 years within the observed time frame, with one-third of the sampling classified as normal drought and two instances categorized as severe events according to the Standardized Precipitation Index (SPI). Our findings suggest that the Pearson type III distribution is the most appropriate for estimating the return periods of extreme precipitation in Taza, whereas the Gumbel distribution is better suited for Sebt Boukellal. We record precipitation levels of 45 mm in Taza and 54 mm in Sebt Boukellal for a return period of 5 years and rise to 88 mm in Taza and 95 mm in Sebt Boukellal for a return period of 100 years.